Fourth IFIP International Conference on Theoretical Computer Science- TCS 2006
DOI: 10.1007/978-0-387-34735-6_10
|View full text |Cite
|
Sign up to set email alerts
|

Variations on an Ordering Theme with Constraints

Abstract: Abstract. We investigate the problem of finding a total order of a finite set that satisfies various local ordering constraints. Depending on the admitted constraints, we provide an efficient algorithm or prove NP-completeness. We discuss several generalisations and systematically classify the problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…The proof is based on a reduction from the following problem, which is known to be NP-complete [18].…”
Section: Algorithmic Aspectsmentioning
confidence: 99%
“…The proof is based on a reduction from the following problem, which is known to be NP-complete [18].…”
Section: Algorithmic Aspectsmentioning
confidence: 99%
“…Hence every solution of the learning problem made of these two sentences will be such that C and A occur before B in t 1 . In Section 4, this technique enables us to reduce the problem of betweenness [12] to our grammar lifting problem. This problem is known to be NP-complete.…”
Section: An Examplementioning
confidence: 99%
“…Proof. We give a reduction of the betweenness problem [12] to our grammar induction problem. The betweenness problem is as follows.…”
Section: Learning Pivotal Categories From Compact Closed Categories Tmentioning
confidence: 99%
“…Guttmann and Maucher [32] showed that there are in fact only 13 distinct Π-CSP's of arity 3 up to symmetry, of which 11 are nontrivial. They are listed in Table 1 together with their complexity.…”
Section: Ordering Cspsmentioning
confidence: 99%